PREDICTING THE EFFICIENCY OF COMMERCIAL BANKS IN BANGLADESH - Solaiman, Md. Golam; Chowdhury, Md. Shahnur Azad; Hossain, Basharat; Akter, Sultana; Azam, Md. Kazi Golam (International Journal of Accounting & Finance Review, 2021)
This paper examines the efficiency of the thirty-six commercial banks (27 Domestic and 9 Foreign Banks) by reviewing Literature and analyzing 6 years (2011-2016) data. The sample was selected based on the availability of data. It is assumed that the banking sector complies with the variable returns to scale (VRS) approach which means the output of a bank is not proportionately related to its inputs. Therefore, VRS in the ‘Data Envelop Analysis (DEA)’ technique has been employed in this paper. The findings reveal that most (30 banks out of 36 banks) of the banks of Bangladesh are inefficient in terms of technical, allocative, and scale efficiency during the 2011-2016 periods. Conversely, only six banks (4 domestic banks and 2 foreign banks) were found efficient in overall scores in this scrutinization. This study did not find any single bank as efficient in all categories (allocative efficiency, technical efficiency, pure efficiency ratio) for the whole study period (2011-2016). This paper provides valuable intuition, analysis, and comments to the managers and policymakers of the bank’s efficiency score so that they comprehend their position. Finally, this paper suggests necessary steps to transform the inefficient banks into efficient banks, and to make stable the banking sector of Bangladesh. JEL Classification Codes: E51, G21, M1.